HIL Simulation of a Rectifier with Power Factor Correction - Kiffe, Axel; Schulte, Thomas
Power electronic devices are growing in importance in automotive applications. Power converters are used in hybrid electric vehicles but also in other vehicle applications like electric steering systems for example. For testing electronic equipment, hardware-in-the-loop simulation is a today’s standard method in the automotive industry. Hardware-in-the-loop simulation requires a real-time capable model of the plant but the development of those models of power electronic circuits is still an ambitious task due to the switching of the semiconductors devices. Real-time simulation usually requires a fixed step-size which does not allow classic zero crossing detection algorithms. Depending on the chosen real-time platform, the minimum possible step-size of the real-time simulation is limited and requires special algorithms for an appropri-ate and precise simulation of these high dynamic systems. In this contribution, a hardware-in-the-loop simulation of a rectifier with power factor correction will be presented. First a short outline on modelling methods for real-time simulation of power electronics is given and an approach for determining the model as well as the necessary assumptions and simplifications are described. Finally, the hardware-in-the-loop bench is described and measurement results from the real plant and the simulation results are compared.